Acrodermatitis continua of Hallopeau: clinical perspectives - Smith MP; Ly K; Thibodeaux Q; Bhutani T; Liao W; Beck KM (Dove Medical Press, 2019)
Mary Patricia Smith, Karen Ly, Quinn Thibodeaux, Tina Bhutani, Wilson Liao, Kristen M BeckDepartment of Dermatology, University of California, San Francisco, CA, USAAbstract: Acrodermatitis continua of Hallopeau (ACH) is a rare, sterile pustular eruption of one or more digits. The condition presents with tender pustules and underlying erythema on the tip of a digit, more frequently arising on a finger than a toe. As far as classification, ACH is considered a localized form of pustular psoriasis. The eruption typically occurs after local trauma or infection, but such a history is not always present and various other etiologies have been described including infectious, neural, inflammatory, and genetic causes. The natural progression of ACH is chronic and progressive, often resulting in irreversible complications such as onychodystrophy that can result in anonychia, as well as osteitis that can result in osteolysis of the distal phalanges. Because of the rarity of ACH, there have been no randomized controlled studies to evaluate therapies, resulting in an absence of standardized treatment guidelines. In clinical practice, a wide variety of treatments have been attempted, with outcomes ranging from recalcitrance to complete resolution. In recent years, the introduction of biologics has provided a new class of therapy that has revolutionized the treatment of ACH. Specifically, rapid and sustained responses have been reported with the use of anti-tumor necrosis factor agents like infliximab, adalimumab, and etanercept; IL-17 inhibitors like secukinumab; IL-12/23 inhibitors like ustekinumab; and IL-1 inhibitors like anakinra. Nevertheless, there remains a considerable need for more research into treatment for the benefit of individual patients with ACH as well as for the clinical knowledge gained by such efforts. The purpose of this review is to provide a comprehensive overview of the key features of ACH as well as a discussion of clinical management strategies for this unique and debilitating condition.Keywords: acrodermatitis continua of Hallopeau, psoriasis, pustular psoriasis, generalized pustular psoriasis, palmoplantar pustulosis